A new species from Türkiye:Ferula erzincanica (Ferulinae, Apiaceae) - SAĞIROĞLU, Mehmet; BANİ, Barış; DUMAN, Hayri (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2025)
In this study, Ferula erzincanica, a new species from East Anatolia, is described and illustrated. The new species shows significant differences from F. rigidula and F. divaricata, particularly by in the dissection of basal leaves, the length and orientation of the inflorescence branches, the length of the pedicels, the undulation of the dorsal wings of the mericarps, and the number of commissural vittae, as well as in the micromorphology of fruits as analyzed by SEM (Scanning Electron Microscopy). In addition, Maximum Likelihood (ML) and Bayesian Inference (BI) phylogenetic analyses based on the nrDNA ITS gene region were performed to determine the phylogenetic position of the new species within the broad sampling of the genus. IUCN Red List assessment and a distribution map are also provided.